The effect of deformation of flow part of elastomeric elements of self-acting valves on characteristics of low-speed long-stroke compressor stages - I. S. Busarov; S. S. Busarov; V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The results of the study of the influence of changes in the area of the flow section in the seat of selfacting valves with elastomeric elements on the characteristics of low-speed compressor stages are presented. A method of experimental research of low-speed compressor stages with the possibility of obtaining instantaneous parameters of the gas state in the working chamber of the stage and its integral characteristics and an experimental stand for its implementation have been developed. The results of comparative experimental studies have confirmed the effectiveness of the valve design with a variable cross-sectional area of the seat in comparison with known designs — an increase in the feed coefficient and isothermal indicator efficiency is at least 10...15%.